PENGAJARAN KOSA KATA BAGI MAHASISWA EFL DENGAN MENGGUNAKAN GAME - gaguk rudianto; Yessie Aldriani (BASIS (Bahasa dan Sastra Inggris), 2018)
Regardless of the vocabulary teaching in EFL students is neglected, the role of vocabulary becomes more and more essential in both second language teaching more over foreign language one. Putting off vocabulary teaching happens because many English teachers are not confident enough to decide both method and technique of teaching vocabulary. This paper is written to give interesting alternative of vocabulary teaching technique with the hope to meet challenge of teaching vocabulary